All Days 2011
DOI: 10.2118/143331-ms
|View full text |Cite
|
Sign up to set email alerts
|

Inversion of DTS Logs To Measure Zonal Coverage During and After Wellbore Treatments With Coiled Tubing

Abstract: Distributed temperature sensing (DTS) is a fiber-optic technology that provides continuous temperature profiles along the length of a well. When placing the fiber inside a coiled tubing (CT), one can monitor the temperature evolution while pumping, as well as during a shut-in period. This evolution, in turn, yields some indications about the fluid placement performance or zonal coverage. So far, interpretation of such DTS traces has mostly been qualitative. The work presented here demonstrates how DTS data can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Duru and Horne (2010) made use of DTS data for estimating formation parameters, such as permeability and porosity, among others, during transient testing. Muradov and Davies (2011), Li et al (2011), andTardy et al (2012), among others, demonstrated the use of distributed measurements in zonal contribution assessment in horizontal wells. The coupled nature of fluid and heat flows in transient testing of gas wells has been the subject of many studies.…”
Section: Introductionmentioning
confidence: 99%
“…Duru and Horne (2010) made use of DTS data for estimating formation parameters, such as permeability and porosity, among others, during transient testing. Muradov and Davies (2011), Li et al (2011), andTardy et al (2012), among others, demonstrated the use of distributed measurements in zonal contribution assessment in horizontal wells. The coupled nature of fluid and heat flows in transient testing of gas wells has been the subject of many studies.…”
Section: Introductionmentioning
confidence: 99%